1994
DOI: 10.1136/bmj.309.6969.1605
|View full text |Cite
|
Sign up to set email alerts
|

Heart muscle disease related to HIV infection: prognostic implications

Abstract: Objectives-To determine the natural course of heart muscle disease in patients infected with HIV.Design-Prospective echocardiographic survey and observational study over four years.Setting-Edinburgh. Subjects-296 adults infected with HIV (mean age 32-7 years (range 21P5 to 67 6) drawn from an the major groups at risk ofHIV infection in Britain.Main outcome measures-Detection of myocardial dysfunction and time to death from index echocardiogram in serial echocardiography.Results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1
12

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 17 publications
3
86
1
12
Order By: Relevance
“…In this study, there was no significant linear correlation between CD4 count and parameter for cardiac manifestations. Herskowitz et al reported 9 patients experiencing symptomatic heart disease, all of them having CD4 T cell counts <200 mm 3 , which represented a significant factor in predicting cardiac disease in HIV infected patents. 20 Cardoso et al also reported that HIV infected patients with CD4+ lymphocytes counts < or = 100/mm 3 had more frequent abnormal echocardiograms than those with CD4+ lymphocytes counts > 100/mm 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, there was no significant linear correlation between CD4 count and parameter for cardiac manifestations. Herskowitz et al reported 9 patients experiencing symptomatic heart disease, all of them having CD4 T cell counts <200 mm 3 , which represented a significant factor in predicting cardiac disease in HIV infected patents. 20 Cardoso et al also reported that HIV infected patients with CD4+ lymphocytes counts < or = 100/mm 3 had more frequent abnormal echocardiograms than those with CD4+ lymphocytes counts > 100/mm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In developing countries, where HAART is not widely available, an increase has been noted in the prevalence of cardiomyopathy and pericardial effusion, with a related high mortality rate for congestive heart failure. 3 In the context of these new clinical findings, it has been observed in developed countries that some HAART regimens, especially those including protease inhibitors, may cause an iatrogenic metabolic syndrome (HIV-associated lipodystrophy syndrome) that is associated with an increased risk for cardiovascular events (myocardial infarction and stroke) because of a process of accelerated atherosclerosis. The most important clinical application of HIV-related immunology is measurement and interpretation of the absolute CD4 cell count.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, quantification of RRV can be regarded as a measurement of the autonomicmediated cardiovascular homeostasis, a marker of cardiovascular prognosis (24,26,27). Accordingly, reduction in RRV-related indexes represents autonomic impairment and involves a poor prognosis (9,24,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, amongst cardiac abnormalities detected in children with acquired immune deficiency syndrome, mild systolic and diastolic impairments, autonomic nervous system disturbances, cardiac arrhythmias and sudden death have been noteworthy (7)(8)(9)(10)(11)(12)(13). On the other hand, some echocardiographic abnormality has been detected in 1 of 4 HIV-positive children and data regarding cardiac autonomic function in the pediatric population are lacking (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%